Mesenchymal Stem Cells Derived from Human Exocrine Pancreas Spontaneously Express Pancreas Progenitor-Cell Markers in a Cell-Passage-Dependent Manner - Song Lee; Seonghee Jeong; Chanmi Lee; Jooyun Oh; Song-Cheol Kim (Stem Cells International)
Mesenchymal stem cells (MSCs) derived from bone marrow, adipose tissue, and most connective tissues have been recognized as promising sources for cell-based therapies. MSCs have also been detected in human pancreatic tissue, including endocrine and exocrine cells. These adult human pancreas-derived MSCs have generated a great deal of interest owing to their potential use in the differentiation of insulin-producing cells for diabetes treatment. In the present study, we isolated MSCs from the adult human exocrine pancreas to determine whether isolated MSCs have the potential to differentiate into pancreatic endocrine cells and, therefore, whether they can be used in stem cell-based therapies. Pancreatic tissue was digested by collagenase and an enriched exocrine-cell fraction was obtained by density-gradient separation. Crude exocrine cells were methodically cultured in suspension and then in adherent culture. We expanded the human pancreatic exocrine-derived MSCs (hpMSCs) by cell passaging in culture and confirmed by flow cytometry that >90% expressed human classic surface markers of MSCs. Interestingly, these cells expressed pancreatic transcription factors, such as Pdx1, Ngn3, and MafA, similar to pancreatic progenitor cells. These results indicated that hpMSCs can be used for the differentiation of pancreatic endocrine cells and may be used in type 1 diabetes treatment.